Ferulic acid inhibits interleukin 17‐dependent expression of nodal pathogenic mediators in fibroblast‐like synoviocytes of rheumatoid arthritis. Issue 2 (30th August 2018) - Ganesan, Ramamoorthi; Rasool, Mahaboobkhan
Abstract: Interleukin 17 (IL‐17), a proinflammatory cytokine produced by T helper (Th) 17 cells, potentially controls fibroblast‐like synoviocytes (FLS)‐mediated disease activity of rheumatoid arthritis (RA) via IL‐17/ IL‐17 receptor type A (IL‐17RA)/signal transducer and activator of transcription 3 (STAT‐3) signaling cascade. This has suggested that targeting IL‐17 signaling could serve as an important strategy to treat FLS‐mediated RA progression. Ferulic acid (FA), a key polyphenol, attenuates the development of gouty arthritis and cancer through its anti‐inflammatory effects, but its therapeutic efficiency on IL‐17 signaling in FLS‐mediated RA pathogenesis remains unknown. In the current study, FA markedly inhibited the IL‐17‐mediated expression of its specific transmembrane receptor IL‐17RA in FLS isolated from adjuvant‐induced arthritis (AA) rats. Importantly, FA dramatically suppressed the IL‐17‐mediated expression of toll‐like receptor 3 (TLR‐3), cysteine‐rich angiogenic inducer 61 (Cyr61), IL‐23, granulocyte‐macrophage colony stimulating factor (GM‐CSF) in AA‐FLS via the inhibition of IL‐17/IL‐17RA/STAT‐3 signaling cascade. In addition, FA significantly decreased the formation of osteoclast cells and bone resorption potential in a coculture system consisting of IL‐17 treated AA‐FLS and rat bone marrow derived monocytes/macrophages. Furthermore, FA remarkably inhibited the IL‐17‐mediated expression of receptor activator of nuclear factor κ‐Β ligand (RANKL) and increased the expression of osteoprotegerin (OPG) in AA‐FLS via the regulation of IL‐17/IL‐17RA/STAT‐3 signaling cascade. The therapeutic efficiency of FA on IL‐17 signaling was further confirmed by knockdown of IL‐17RA using small interfering RNA or blocking of STAT‐3 activation with S3I‐201. The molecular docking analysis revealed that FA manifests significant ligand efficiency toward IL‐17RA, STAT‐3, IL‐23, and RANKL proteins. This study provides new evidence that FA can be used as a potential therapeutic agent for inhibiting IL‐17‐mediated disease severity and bone erosion in RA. Abstract : Ferulic acid inhibits osteoclastogenesis via the regulation of Interleukin (IL)‐17/IL‐17 receptor type A/signal transducer and activator of transcription 3‐dependent expression of receptor activator of nuclear factor κ‐Β ligand and osteoprotegerin in adjuvant‐induced arthritis fibroblast‐like synoviocytes.